An Examination of UV-Induced Bystander Effects and the Repair of a UV-Damaged Reporter Gene in Human Cells - Rybak, Adrian (My University, 2005)
We have used a non-replicating recombinant adenovirus, AdCA17𝘭𝘢𝘤𝘡, which expresses the β-galactosidase (β-gal) reporter gene under the control of the human cytomegalovirus immediate early (HCMV-IE) promoter, to examine host cell reactivation (HCR) of a UVC-damaged reporter gene in human fibroblasts. Since β-gal expression in mammalian cells is expected to occur following transcription of a lesion-free 𝘭𝘢𝘤𝘡 reporter gene, the removal of UV-induced DNA lesions and subsequent β-gal expression is a measure of the DNA repair capacity of the infected cell. In the present work, we have examined HCR and UV-enhanced HCR of the UV-damaged reporter construct, AdCA17𝘭𝘢𝘤𝘡, in normal and nucleotide excision repair (NER) deficient fibroblasts. Xeroderma pigmentosum (XP) group C and E fibroblasts are deficient in the global genome pathway (GGR) of NER, while Cockayne syndrome (CS) fibroblasts are deficient in the transcription-coupled repair pathway (TCR) of NER and XP group A fibroblasts are deficient in both TCR and GGR. HCR of the UV-damaged reporter gene activity was significantly reduced in XP-A, XP-C, XP-E and CS-B cell strains relative to that in normal human fibroblasts, indicating that both TCR and GGR contribute to expression of the UV-damaged reporter gene in human cells. Pre-treatment of human fibroblasts with UVC (12 J/m²) immediately prior to infection results in enhanced HCR of the UV-damaged reporter gene. UV-enhanced HCR of the UV-damaged reporter gene was detected in normal fibroblasts at 12 hr post-infection and in CS-B, XP-C and XP-E fibroblasts, but not XP-A fibroblasts at 24 and 40 hr post-infection. These results indicate that both TCR and GGR are UV-inducible in human cells. We have examined the colony survival of various human cells following exposure to UVC and UVA radiation. HaCAT, an immortalized human keratinocyte cell line, demonstrated increased resistance to UVC exposme compared to glioma (U373, T98G) and colon carcinoma (HT29) cell lines, while exhibiting increased sensitivity to UVA radiation and H₂O₂ treatment. This increased sensitivity towards both UVA and H₂O₂ treatment suggests that HaCAT cells have a reduced capacity to repair oxidative DNA damage. In addition, we show that p53-null keratinocytes (HPV-G) have reduced clonogenic survival compared to p53-mutant keratinocytes (HaCAT) following H₂O₂ treatment, consistent with an involvement of p53 in the survival of keratinocytes following H₂O₂ treatment. We also examined whether the interaction of H₂O₂ with growth media resulted in chemical by-products that were toxic to cells. Even though the H₂O₂ levels in the media were reduced following 24 hr incubation, similar clonogenic survival curves of HaCAT cells were observed following treatment of cells with immediately-prepared or 24hr-incubated H₂O₂-containing media solutions. Thus, extended incubation (24 hr) of H₂O₂ with media did not alter its cytotoxicity towards HaCAT cells, indicating that no detectable levels of toxic chemical by-products were produced. Ultraviolet irradiation of cells can have both cytotoxic and/or mutagenic consequences, resulting in increased levels of cell death or the induction of a state of genomic instability that persists for several cell generations after irradiation. However, the extent of the effects induced in non-irradiated cells by UV -irradiated cells has not been fully investigated. Using the medium transfer technique, we have tried to address whether UV irradiation of cells can induce biological effects in non-irradiated cells. Medium obtained from UVA, but not UVC, irradiation of various human cell lines in phosphate-buffered saline (PBS) solution was capable of reducing the relative clonogenic survival and colony size of non-irradiated HaCAT cells. In the absence of cells, UVA-irradiation of PBS reduced the clonogenic survival, but not the colony size, of various non-irradiated human cells. These results indicate a cytotoxicity of UVA-irradiated PBS towards non-irradiated cells. Hydrogen peroxide, a reactive oxygen species (ROS) generated following UV A irradiation, was measured following UV A treatment (or mock-treatment) of PBS (in the presence or absence of cells) either immediately or 24 hr post-irradiation. Hydrogen peroxide levels increased immediately following UV A irradiation, suggesting that it may contribute to the reduced survival of non-irradiated human cells. However, human glioma T98G and U373 cells produced elevated H₂O₂ levels in mock-irradiated conditions at 24 hr post-incubation, while demonstrating different sensitivities towards treatment with medium containing UVA-irradiated PBS. These results suggest that UVA-induced H₂O₂ is not responsible for the reduction in clonogenic survival of non-irradiated human cells. We also examined colony number and size at different times following the addition of media containing UVA-irradiated PBS and media from UVA-irradiated cell cultures. Increasing the time before scoring for colonies resulted in an increased clonogenic survival and a decrease in relative colony size for HaCAT cells. These preliminary results suggest that the relative survival and relative colony size of non-irradiated cells are inter-related, and indicate that treating non-irradiated HaCAT cells with medium from UVA-irradiated cells or medium containing UVA-irradiated PBS reduced the growth rate of HaCAT colonies. Therefore, in order to properly evaluate clonogenic survival, a time-dependent examination of relative survival and relative colony size should be conducted in order to address whether the treatment results in an inhibition of cell growth and/or true cell killing.
Bystander Effects and DNA Repair Following UV Exposure
Keywords: UV; bystander; repair; human; cell